Isolation, Screening, and Characterization of Biosurfactant-Producing Microorganisms from Petroleum-Contaminated Soil and Further Optimization of Parameters for Biosurfactant Production: Isolation, Screening, and Characterization of Biosurfactant-Producing Microorganisms from Petroleum-Contaminated Soil and Further Optimization of Parameters for Biosurfactant Production - Rana, Dr. Pooja (International Journal of Pharmaceutical & Biological Archive, 2018)
Introduction: Biosurfactants are amphiphatic in nature and are surface-active compounds produced by microorganisms. These molecules reduce interfacial surface tension between aqueous solutions and hydrocarbon mixtures. Unfortunately, oil spills and industrial discharges from petroleum-related industries have been identified as the major pollution sources. The hydrophobicity and low aqueous solubility of petroleum pollutant limit the biodegradation process. The features that make biosurfactants as an alternative to commercially synthesized surfactants are its low toxicity, higher biodegradability and, hence, greater environmental compatibility, better foaming properties, and stable activity at extreme pH, temperature, and salinity. Objective: Therefore, in this study, hydrocarbon-degrading bacteria were screened from petroleum-contaminated soil, characterized and optimization of the physical and nutrient parameters were done to enhance the production of biosurfactants. Results: Petroleum-contaminated soil was collected from different petrol pumps in Pune and screening was done on minimal salt medium media containing palm oil as carbon source using hemolytic activity, emulsification index, drop-collapse test, and oil displacement method. The most promising strain was isolated and identified using Bergeyâ€™s Manual of Determinative Biology and 16s rRNA sequencing and was found to be Staphylococcus epidermidis. The optimization of various parameters, namely temperature, pH, carbon, and nitrogen sources on growth, and biosurfactant production was studied. The highest biosurfactant production was obtained when MSS media contains sucrose (carbon source) and urea (nitrogen source) at pH 10 and temperature 55Â°C. The Fourier transform-infrared (FT-IR) analysis of purified biosurfactant indicated the presence of lipopeptide biosurfactant when compared with reference FT-IR spectra.